Multi-agent interaction of source, load and storage to realize peak shaving and valley filling under the guidance of the market mechanism - Wang, Chunhui; Wu, Zhigang; Lin, Zihui; Liu, Jianing (Frontiers in Energy Research, 2023)
In the construction of new power system, traditional methods and capabilities for regulating the power grid are no longer applicable due to the increasing types and quantities of source, load and storage agents. Currently, research on the participation of these agents in the electricity market has mainly focused on either traditional power systems or the demand side, without exploring the potential interaction between them. To address this issue, this paper proposes a real-time pricing regulation mechanism that incorporates source, load and storage agents into regulation. This mechanism is suitable for new power systems and satisfies the interests of the agents while meeting the needs of grid regulation. Specifically, it is based on time-of-use and real-time pricing regulation mechanisms. In a simulated scenario of load shifting, the proposed pricing regulation mechanism effectively meets the grid regulation requirements and improves the stability of grid operation. Overall, this approach offers a promising solution for the regulation of new power system with diverse and complex agents.